Assessing the impact of artificial geotextile covers on glacier mass balance and energy fluxes - Yi-Da Xie; Fei-Teng Wang; Hui Zhang; Wen-Tao Du; Wei-Bo Zhao (Advances in Climate Change Research)
As global warming accelerates, leading to the retreat of glaciers, the effectiveness of artificial coverings, in particular geotextiles, in reducing glacier ablation has emerged as a topic of increasing concern. Nevertheless, a critical gap in knowledge persists regarding the specific physical processes involved in the mitigation provided by these coverings. This study explores the underlying mechanisms that govern the interaction through field observations and COSIPY model simulations at Bailanghe Glacier No. 21 in the Qilian Mountains from 26 June to September 17, 2023. It compares covered and uncovered areas to evaluate differences in mass and energy balance fluxes. It was discovered that geotextiles could decrease ice melt by up to 1000 mm w.e. in comparison to the surface of glaciers without cover, primarily because of a 23% increase in albedo compared to ice, leading to a decrease in net short-wave radiation and available melt energy. The effect of covering the entire glacier with a geotextile, which has varying albedo properties, was also simulated. It was found that, with every 5% increase in the albedo of the geotextile, ablation was reduced by 10%–25%, resulting in a decrease in ice volume loss of approximately 2.5 × 105 m3. While artificially covering glaciers can reduce ablation rates, it faces challenges such as high costs, environmental risks, and issues with replicability. Ultimately, this study aims to analyze the feasibility of glacier coverage from a mechanistic perspective for glacier management amidst ongoing climate change.